LAYANAN CLOUD COMPUTING BERBASIS INFRASTRUCTURE AS A SERVICE MENGGUNAKAN ANDROID - Hero Wintolo; Lalu Septian Dwi Paradita (Institut Teknologi Dirgantara Adisutjipto, 2015)
Cloud computing, one form of information technologies are widely used in the field of computer networks or the Internet. Cloud computing consists of computer hardware, computer networking devices, and computer software, the cloud computing there are three services provided include (SaaS) Software as a Service (PaaS) Platform as a Service, and (IaaS) Infrastructure as a Service. Application cloud computing services in the wake of this system is a service-based data storage infrastructure as a service by using android smartphone as a storage medium, which utilizes FTP Server which is already available on the smartphone. This certainly supports the easy storage of data that utilize various types of internal and external storage on smartphones that serves as a storage server. In addition to the functions of storage available, this service can accommodate streaming function .mp3 file type. Implementation result of the system can be implemented on a local network using a wireless LAN. In addition, the results of user testing using Likert method shows the application can run and function properly